Intrapericardial antibiotics and fibrinolysis to shorten course of antibiotics and prevent constrictive pericarditis in acute purulent pericarditis due to staphylococcus aureus - Sharma, Neeraj; Karki, Parag (Nepalese Heart Journal, 2023)
Acute purulent pericarditis, although rare in modern antibiotic era, is a life-threatening condition requiring timely diagnosis and aggressive treatment modalities. We report a successfully treated previously healthy immunocompetent 23 years old male patient diagnosed as secondary acute purulent pericarditis caused by methicillin sensitive Staphylococcus aureus with a primary skin abscess. The patient initially presented with complains of fever, chest pain and occasional cough with no significant finding in clinical examination. Electrocardiography showed widespread ST elevation and echocardiography revealed fluid collection with echogenic floaters in pericardial space. Diagnostic pericardiocentesis was done and fluid showed growth of methicillin sensitive Staphylococcus aureus. The patient was managed with anti-inflammatory drugs, appropriate intravenous antibiotic for two weeks, therapeutic pericardiocentesis with intrapericardial vancomycin instillation and fibrinolysis with alteplase to prevent constrictive pericarditis and persistent purulent pericarditis. The patient was followed up in three months and was found to have no residual disease or complication.